Journalists at work - revisited - Tumber, Howard (Javnost (Ljubljana), 2006)
This article takes the opportunity to look in more detail at one of Jeremy Tunstall's seminal works - Journalists at Work published in 1971. It was the first major social science study of specialist journalists in the UK. Tunstallbegan the research in 1965 at a time when no single social science study of British journalism existed. Tunstall's study of British journalism set out to investigate specialist news gatherers on national newspapers constituting approximately fifteen per cent of the personnel in those organisations and representing about two percent of all British journalists. Three aspects of Tunstall's study are discussed: news organisations and their goals, the source-media relationship, and the occupation of journalism in addition to some comments about the context and the methodology of the research.
Keywords: Thunstall, Jeremy; novinarji; novinarstvo; journalism; časniki; dnevniki; novice; objektivnost; novinarska etika; mass media; množični mediji; vplivi